ChemInform Abstract: Molecular Switching Involving Metastable States: Molecular Thermal Hysteresis and Sensing of Environmental Changes by Chiral Helicene Oligomeric Foldamers. Issue 20 (April 2016) - Shigeno, Masanori; Kushida, Yo; Yamaguchi, Masahiko
Abstract: Review: [39 refs.